2019
DOI: 10.1007/s00210-019-01732-0
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of proteins of human skin fibroblasts is changed by rosmarinic acid

Abstract: Glycosylation is a common post-translational process of protein modification. Glycans participate in many crucial biological functions like cell differentiation, cell adhesion, cell-cell interactions, and regulation of signaling pathways. Rosmarinic acid (RA) is a natural flavonoid with many pharmacological activities including anti-inflammatory, anti-oxidative, anti-bacterial, or anti-fibrotic. In this study, we aimed to determine the effect of 25, 50, and 100 μM rosmarinic acid on specific carbohydrate antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, the water solubility of the Orthosiphol A is poor, and the gastrointestinal absorption is low in our ADMET model. Different from Orthosiphol A, Rosmarinic acid, a water-soluble and absorbable polyphenol that been researched endlessly, had several exciting effects, including antioxidant(Shen et al, 2017), anti-inflammatory(Luo et al, 2020), anti-tumor(Kim et al, 2015), antimicrobial(Slobodnikova et al, 2013), anti-diabetic(Ngo et al, 2018), neuroprotective(Ghasemzadeh and Hosseinzadeh, 2020; Hasanein and Mahtaj, 2015) and nephroprotective activities(Domitrovic et al, 2014; Al-Dhabi et al, 2014) even cosmetic effects(Iwona and Katarzyna, 2020). Similarly, two flavonoids Eupatorin and Sinensetin also been confirmed to possess almost the same pharmacological effects as O. aristatus (Han et al, 2020; Laavola et al, 2012; Chung et al, 2020; Ashraf et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the water solubility of the Orthosiphol A is poor, and the gastrointestinal absorption is low in our ADMET model. Different from Orthosiphol A, Rosmarinic acid, a water-soluble and absorbable polyphenol that been researched endlessly, had several exciting effects, including antioxidant(Shen et al, 2017), anti-inflammatory(Luo et al, 2020), anti-tumor(Kim et al, 2015), antimicrobial(Slobodnikova et al, 2013), anti-diabetic(Ngo et al, 2018), neuroprotective(Ghasemzadeh and Hosseinzadeh, 2020; Hasanein and Mahtaj, 2015) and nephroprotective activities(Domitrovic et al, 2014; Al-Dhabi et al, 2014) even cosmetic effects(Iwona and Katarzyna, 2020). Similarly, two flavonoids Eupatorin and Sinensetin also been confirmed to possess almost the same pharmacological effects as O. aristatus (Han et al, 2020; Laavola et al, 2012; Chung et al, 2020; Ashraf et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the water solubility of the Orthosiphol A is poor, and the gastrointestinal absorption is low in our ADMET model. Different from Orthosiphol A, Rosmarinic acid, a water-soluble and absorbable polyphenol that been researched endlessly, had several exciting effects, including antioxidant 35 , anti-inflammatory 36 , anti-tumor 37 , antimicrobial 38 , anti-diabetic 39 , neuroprotective 40,41 and nephroprotective activities 42,43 even cosmetic effects 44 . Similarly, two flavonoids Eupatorin and Sinensetin also been confirmed to possess almost the same pharmacological effects as O. aristatus 4,[45][46][47] .…”
Section: Other Conditionsmentioning
confidence: 99%
“…This fructose concentration correlates to the minimum concentration needed for in vitro DNA glycation 49 . It has also been shown that 25 μM rosmarinic acid reduces the glycosylation of human broblasts in vitro 50 . 0.02 % (w/v) NaN3 was added to the solution and puri ed into a low proteinbinding lter (-GV 0.22 µm lter unit, Millipore) to avoid bacterial contamination.…”
Section: Methodsmentioning
confidence: 96%
“…This fructose concentration correlates to the minimum concentration needed for in vitro DNA glycation 49 . It has also been shown that 25 µM rosmarinic acid reduces the glycosylation of human fibroblasts in vitro 50 . 0.02% (w/v) NaN3 was added to the solution and purified into a low protein-binding filter (-GV 0.22 µm filter unit, Millipore) to avoid bacterial contamination.…”
Section: Methodsmentioning
confidence: 97%